Copy number variation: A prognostic marker for young patients with squamous cell carcinoma of the oral tongue. (2nd November 2018) - Gu, Xiaolian; Coates, Philip J.; Boldrup, Linda; Wang, Lixiao; Krejci, Adam; Hupp, Ted; Fahraeus, Robin; Norberg‐Spaak, Lena; Sgaramella, Nicola; Wilms, Torben; Nylander, Karin
Abstract : Background: The incidence of squamous cell carcinoma of the oral tongue (SCCOT) is increasing in people under age 40. There is an urgent need to identify prognostic markers that help identify young SCCOT patients with poor prognosis in order to select these for individualized treatment. Materials and methods: To identify genetic markers that can serve as prognostic markers for young SCCOT patients, we first investigated four young (≤40 years) and five elderly patients (≥50 years) using global RNA sequencing and whole‐exome sequencing. Next, we combined our data with data on SCCOT from the cancer genome atlas (TCGA), giving a total of 16 young and 104 elderly, to explore the correlations between genomic variations and clinical outcomes. Results: In agreement with previous studies, we found that SCCOT from young and elderly patients was transcriptomically and also genomically similar with no significant differences regarding cancer driver genes, germline predisposition genes, or the burden of somatic single nucleotide variations (SNVs). However, a disparate copy number variation (CNV) was found in young patients with distinct clinical outcome. Combined with data from TCGA, we found that the overall survival was significantly better in young patients with low‐CNV (n = 5) compared to high‐CNV (n = 11) burden ( P  =   0.044). Conclusions: Copy number variation burden is a useful single prognostic marker for SCCOT from young, but not elderly, patients. CNV burden thus holds promise to form an important contribution when selecting suitable treatment protocols for young patients with SCCOT.